ANALYSIS OF QUALITY CONTROL IN THE AMPLANG PRODUCTION PROCESS TO MINIMIZE DEFECTS USING THE SEVEN TOOLS METHOD: A CASE STUDY AT MSME (AMPLANG LILY) - Nurul Hidayat; Alfian Rizky Desta Pratama; Andi Yetni Widyani; Juana Melen Amelda (Universitas Nusa Cendana, 2026)
Amplang is a traditional Indonesian snack made from milkfish and is widely recognized for its distinctive taste and crunchy texture. In an increasingly competitive food industry, maintaining consistent product quality is essential to meeting consumer expectations and sustaining market competitiveness. This study aims to analyze quality control practices in the amplang production process at Amplang Lily, with a particular focus on reducing product defects. The research employs the Seven Quality Control Tools, including flowcharts, check sheets, histograms, scatter diagrams, fishbone diagrams, Pareto charts, and control charts, which are applied across various stages of the production process. The findings reveal that product defects are primarily attributable to substandard raw materials, inaccurate ingredient measurements, improper processing techniques, and human error during production. This study is limited to a single case study at Amplang Lily, which may restrict the generalizability of the findings to other similar enterprises. Therefore, future research is recommended to examine the application of quality control tools across a broader range of small and medium-sized enterprises (SMEs) or in the production of similar products using different raw materials. Keywords: Amplang; Quality Control; Seven Tools